MEMAHAMI ISLAM SECARA UTUH DAN IMPLIKASINYA DALAM DUNIA PENDIDIKAN; KAJIAN PENDEKATAN FENOMENOLOGIS ANNEMARIE SCHIMMEL - Junaidi Junaidi; Hasanah Hasanah (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Islam is an religion that is not only on the social and theological doctrine, but also has an glorious civilization. Because of that, the number of experts who study about Islam produce various definition. That matter also create variant interpretation and understanding. One thing that must be noticed is when religious radicalism grow and negative stigma to Islam. In the same aspect, ideology doctrine of religious radicalism having in sight in Indonesia, in other words in the educational institution which the main target is students. Annemarie Schimmel uses fenomenological approach to understand about Islam holistically and disclaim negative stigma about Islam. This approach also create natural thought of an religion based on the religion believer perspective. So the impact can minimize religious radicalism doctrine.